Advanced Control Strategies for Enhancing the Performance of Phase-Shifted Full-Bridge Series Resonant DC–DC Converters in Photovoltaic Micro-Inverters - Geng Qin; Hui Ma; Jianhua Lei; Chuantong Hao (Energies)
This article addresses the challenges of the reduced efficiency in phase-shifted full-bridge series resonant converters (PSFB-SRCs) used within micro-inverters (MIs), especially under light load and high input voltage conditions. To enhance performance, first-order and second-order time-domain equivalent models that accurately predict the output gain across a wide range of operating conditions are developed. A novel control strategy is proposed, featuring turn-on time as a feedback variable, with phase shift angle and dead time as feedforward variables, enabling precise computation of frequency, duty cycle, and phase shift time for digital controllers. This ensures optimal efficiency, stability, and dynamic response, regardless of the load conditions. Experimental results from the prototype confirmed zero-voltage switching under heavy loads and efficient frequency limiting under light loads, achieving a peak efficiency of 97.8% at a 25 V input. Notably, the light load efficiency remained above 90% even at a 50 V input. These contributions significantly advance PSFB-SRC technology, providing robust solutions for high-efficiency MI applications in photovoltaic systems.